DISCRITE MATHEMATICS TRAINING OF PEDAGOGICAL BACHELOR AND MAGISTRACY STUDENTS – THE FUTURE TEACHERS OF MATHEMATICS AND COMPUTER SCIENCE - V. I. Igoshin (Obrazovanie i nauka, 2015)
The research subject concerns the discrete mathematics teaching - a fundamental aspect of training the future teachers of mathematics and computer science. This field of mathematics has had the priority in various practical applications since 1970s and till our days. The paper outlines the model of pedagogical mathematical education including the following disciplines: mathematical logic, discrete mathematics and algorithm theory. The given model is developed for three educational  levels: general education, in-depth bachelor course and post-graduate course,  and is based on the comprehensive analysis of mathematical logic and discrete mathematical ideas and methods incorporated in the school course of mathematics and computer science.The recommended model can be taken as the methodology basis for developing educational plans and curricula for pedagogical higher schools and departments of classical universities to provide the graduates with the application tool of discrete mathematics.